GAMBARAN TINGKAT PENGETAHUAN DAN SIKAP REMAJA PUTRI DALAM MENGHADAPI MENARCHE DI SMP NEGERI 8 KOTA KUPANG - Kadek Dwi Ariesthi (CHMK Applied Science Journal, 2020)
ABSTRACT The lack of good attitude from young women in dealing with Menarche is influenced by several factors, one of which is the level of knowledge. The higher the level of knowledge a teenager has about menarche, the better the attitude or action to be taken in dealing with Menarche. Menarche event is the occurrence of bleeding (menstruation) first on the female genitals because the female glands begin to function, which is to cook the eggs and cooked eggs and then come out of the ovaries (ovaries). This study aims to identify and identify the level of knowledge and attitudes of young women in dealing with Menarche in SMP Negeri 8 Kupang. The research methods used in this research are: (1) Literature study (through scientific essays and documents related to research), (2) Field studies (primary data collection using questionnaires in the form of questionnaires to respondents). The sampling technique uses total sampling, which is sample selection by taking all members of the population to be sampled. The population is all 26 young women who will face Menarche in SMP Negeri 8 Kupang. Data analysis was performed univariately by calculating the distribution and frequency of the studied variables using the relative frequency table and the percentage of each variable using the proportion formula where the numerator divides the denominator. The results of data analysis showed that of the 26 respondents there were 4% of respondents with a good level of knowledge, 23% of respondents with a sufficient level of knowledge and 73% of respondents with insufficient perception. The analysis also shows that there are 69% of respondents with good attitude, 23% of respondents with enough attitude and 8% of respondents with less attitude. Keywords: Level of knowledge, Young Women, Menarche.